Defending a Benefit-Based Approach to Compensation for Necessary Losses - Ferrick, Brandon (Stance: an international undergraduate philosophy journal, 2015)
This paper examines cases when compensation follows from necessary actions that cause harm. I posit that we can determine when compensation is due in instances of necessity by referring to the distribution of benefits and losses that result from the action.